Using Photocatalyst to Enhance Resin Performance in Reducing Carcinogenic Compounds (Future Science, 2021)
Existing techniques of wastewater treatment are not able to remove all water-soluble organic pollutants, including hydrocarbons and a few carcinogens like pesticides, completely, inorganic pollutants, and microbes besides generating secondary chemical pollutants. Therefore, reducing the organic compounds effectively would still require more advanced technology with shorter time and lower cost operations. Using a new innovative material through resin immobilized heterogeneous photocatalyst with UV light or sunlight. The specific objectives are knowing the efficiency of Dowex resin-immobilized heterogeneous photocatalyst ZnO (RIP-ZnO) and photocatalyst TiO2 (RIP-TiO2) for reducing disinfection by-products. RIP-ZnO performed a slightly higher removal of THMs, and HAAs concentration than RIP-TiO2.